2012
DOI: 10.1097/01.sa.0000412400.14133.65
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Apolipoprotein E4 and Postoperative Cognitive Dysfunction in Elderly Patients Undergoing Intravenous Anesthesia and Inhalation Anesthesia

Abstract: A s the population older than 65 years increases, it is possible that advanced age could be used as a barrier to admission for high-level care, especially in the era of resource-limited critical care environments. Difficult decisions regarding access to critical care for the elderly will become increasingly important. Research has found that, in preselected intensive care unit (ICU) cohorts, the severity of illness and acute physiology have a greater effect on prognosis than age alone. Data on patients admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…5 Recently, Cai et al reported that POCD in patients receiving inhalation anesthesia was higher than in patients receiving intravenous anesthesia, particularly in inhalation anesthesia patients harbouring the apolipoprotein E e4 allele associated with Alzheimer's disease. 6 Thus, choice of anesthesia may be an additional factor influencing the incidence of POCD. Several additional clinical studies have also compared the incidence of POCD in patients undergoing intravenous vs inhalation anesthesia.…”
Section: Résumémentioning
confidence: 99%
“…5 Recently, Cai et al reported that POCD in patients receiving inhalation anesthesia was higher than in patients receiving intravenous anesthesia, particularly in inhalation anesthesia patients harbouring the apolipoprotein E e4 allele associated with Alzheimer's disease. 6 Thus, choice of anesthesia may be an additional factor influencing the incidence of POCD. Several additional clinical studies have also compared the incidence of POCD in patients undergoing intravenous vs inhalation anesthesia.…”
Section: Résumémentioning
confidence: 99%
“…Until now, most studies on POCD have been focused on adults, especially elderly patients (1,8,19). Morgan et al (57) were the first to focus on the neuropsychological effects of general anesthesia on pediatric patients, namely, 5 years old children, and reported that children would present cognitive decline after anesthesia with halothane or nitric oxide.…”
Section: Is Pocd Only Related To Old Age?mentioning
confidence: 99%
“…The patient-relevant risk factors reported in previous studies included little education (1), preoperative silent brain ischemia (5), preoperative subclinical dementia (6), pre-existed metabolic syndrome (7), hereditary vulnerabilities such as apolipoprotein E4 (8,9) which is a gene polymorphism of apolipoprotein E, and obesity (10), etc. The possible anesthesia-relevant risk factors included premedication, specific inhaled or intravenous anesthetic agents, the duration and depth of anesthesia, and the imbalances of internal environments such as intraoperative hyperglycemia in non-diabetic patients (11), etc.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Cai et al. should have been included in the final analysis of the effect of intravenous or inhalational anaesthesia on the outcome of postoperative delirium . These corrections do not alter the findings of the meta‐analysis, as the odd ratio (95% CI) for postoperative delirium following intravenous anaesthesia is 1.03 (0.02–59.5) (Fig.…”
mentioning
confidence: 99%